Analysis of the Impact of the Implementation of PSAK 73 on Leases on Financial Performance in Transportation & Logistics sub-sector companies listed on the Indonesia Stock Exchange in 2020-2022 with DER as a Moderating Variable - Fitriyani, Fitriyani; Nugrahanti , Trinandari Prasetyo (West Science Accounting and Finance, 2024)
Growing business and economic activities cause the level of industrial competition to be more competitive. This study aims to analyze the impact of the implementation of PSAK 73 on leases on the financial performance of companies in the transportation & logistics sub-sector listed on the Indonesia Stock Exchange during the period of 2017 - 2022. PSAK 73 was introduced as an accounting standard that regulates the recognition, measurement, and disclosure of rental transactions, which can affect a company's financial statements. The research used is quantitative with a descriptive analysis method by looking at the impact of the implementation of PSAK 73 on the financial performance of companies in the transportation & logistics sub-sector. The data used is sourced from the company's published financial statements listed on the Indonesia Stock Exchange. The results of this study are expected to provide a better understanding of the impact of the implementation of PSAK 73 on the financial performance of companies in the transportation & logistics sub-sector, as well as provide input for practitioners and regulators in facing the implementation of new accounting standards. The results of this study concluded that liability recognition has an effect on financial performance, asset recognition has no effect on financial performance, equity recognition has no effect on financial performance, debt to equity ratio strengthens liability recognition to financial performance, debt to equity ratio strengthens asset recognition Debt to Equity Ratio weakens Equity Recognition to Financial Performance.